MULTI-SCALE MODELING OF TERRITORIAL DYNAMICS OF GEOSPATIAL ANTHROPOGENIC ENERGY CONSUMPTION - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
The development of any region or territory stems from its own dynamic nature. Distribution and consumption of energy resources are varied territorially which in turn is ruled by the number of anthropogenic activities in association with geospatial localization. Such territorial dynamics necessitate considerable modifications of the energy infrastructure. Thus, the development of a computational multi-scale unified energy consumption model with the usage of geographic information help in automating data analysis processes for sustainable urban planning, allocation of energy saving infrastructures and strategic deployment of the renewable energy resources in order to finely regulate the utilization of energy resources for sustainable energy consumption. But the integration of city-wide energy system models and Geographic Information Systems (GIS) is still in its infancy. Thus we propose a computational infrastructure for modeling city wide geospatial energy consumption and automating the data analysis process to provide the sustainable environmental policy which require artificial intelligence based geospatial aware comprehensive planning regarding the modification of the energy supply, consumption, activities and infrastructures in cities. Thus end result of the presented research research work is fine-grained energy demand estimation from data sources, decentralized storage facility and automated sustainable planning; investigation of GIS based anthropogenic activities or mobility pattern influencing the wastage of energy resources, the transition from purely structural to operational planning, and, finally, the development of a new dynamic based power market design.